Duch Święty w katechezie młodzieży ponadgimnazjalnej - Tkocz, Elżbieta (Studia Pastoralne, 2008)
From the point of view of catechising practice since there is the danger of the students’ ignorance of knowledge about the Holy Spirit, His irreplaceable role in leading to a mature faith cannot be neglected. The present study is an attempt to answer the question of what is the role of the Holy Spirit in catechising of secondary school students. Premises, resulting from catechising’s nature and development conditioning, by which the youth is influenced, indicate the need of permanent catechising about the Holy Spirit as He can be a special help to youth experiencing various emotional states connected with changes of a psycho-physical nature, which affect them at this stage of development. To basic tasks of of young people during their secondary school catechising include the acquisitionof the ability of giving testimony to the faith. Essential in fulfilling this aim is teaching the truth about the Holy Spirit, not only in factual matters like knowledge about the Holy Spirit, but especially in matters connected with His personal relations with people. Young Christians will be able to give testimony to the faith only if they accept the Holy Spirit as irreplaceable support to human existence both in social and personal dimensions.